Clinical Features and Virological Correlates of Neurocognitive Impairment among HIV-Infected Individuals in Nigeria - Royal, Walter (2012)
In Nigeria the incidence and prevalence of HIV related neurocognitive impairment (NCI) are unknown and there currently exists little information related to the viral correlates rates of NCI. Therefore studies were performed to examine the potential utility of applying an established neuropsychological (NP) screening battery and detailed NP testing to detect NCI and correlations with functional impairment and the presence of specific viral signatures among infected subjects. 60 HIV-1 seropositive antiretroviral-naive individuals and 56 seronegative control subjects were administered the International HIV Dementia Scale (IHDS) and assessed for functional impairment using the Karnofsky Performance Status Scale. 15 HIV infected patients and 11 controls were also administered a detailed NP battery. Blood samples from 8 infected subjects, 3 with evidence of NCI, were obtained for molecular analysis of HIV-1 strain. Unadjusted scores on the IHDS showed that, using a recommended total score cutoff of 10, 28.8% of the HIV-1 seropositive and 16.0% of seropositive individuals scored abnormally. The mean Karnofsky score for the HIV seropositive and seronegative groups were, respectively, 90.7 +12.2 and 98.8 +3.8 (p<0.0001). Results from testing using the full NP battery showed that overall the HIV seropositive group performed worse than the seronegative group, with effect sizes spanning from small (0.25 on the Trail Making Test A) to large (0.82 on Action Fluency), with an average effect size across the battery of 0.45, which approaches that which has been recorded in other international settings. Finally, sequencing of partial pol amplicons from viral isolates revealed that 2 of 3 patients with NCI were infected with subtype G virus and 1 with the circulating recombinant form (CRF) 02_AG; all 4 individuals without NCI were infected with CRF_02AG. These studies demonstrate the utility of conducting these studies for establishing the burden of NCI in the population of individuals with HIV-1 infection in Nigeria and for assessing the functional consequences and the virologic correlates of NCI.